Geometry of homogeneous bounded domains lectures given at the Centro internazionale matematico estivo (C.I.M.E.) held in Urbino (Pesaro), Italy, July 5-13, 1967 - Vesentini, Edoardo (CIME summer schools, 2011)
Gindikin, I.I. Pjateckii-Sapiro, E.B. Vinberg: Homogeneous Kähler manifolds.- S.G. Greenfield: Extendibility properties of real submanifolds of Cn.- W. Kaup: Holomorphische Abbildungen in Hyperbolische Räume.- A. Koranyi: Holomorphic and harmonic functions on bounded symmetric domains.- J.L. Koszul: Formes harmoniques vectorielles sur les espaces localement symétriques.- S. Murakami: Plongements holomorphes de domaines symétriques.- E.M. Stein: The analogues of Fatous?s theorem and estimates for maximal functions.